2020
DOI: 10.1074/jbc.ac120.013449
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional conservation of the programmed −1 ribosomal frameshift signal of SARS coronavirus 2 (SARS-CoV-2)

Abstract: About 17 years after the severe acute respiratory syndrome coronavirus (SARS-CoV) epidemic, the world is currently facing the COVID-19 pandemic caused by SARS coronavirus 2 (SARS-CoV-2). According to the most optimistic projections, it will take more than a year to develop a vaccine, so the best short-term strategy may lie in identifying virus-specific targets for small molecule–based interventions. All coronaviruses utilize a molecular mechanism called programmed −1 ribosomal frameshift (−1 PRF) to control th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
359
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(411 citation statements)
references
References 24 publications
30
359
3
Order By: Relevance
“…However, our data indicate that the region corresponding to SL2 is conformationally flexible, adopting an SL2 stem with only a 20% probability. Consistent with our reported distribution of structural isoforms, Kelly et al use a reporter assay to suggest that the frequency of successful frameshifting in SARS-CoV-2 is about 20% (Kelly et al, 2020), indicating that the observed conformational variability of SL2 may be functional. Indeed, SL2 might function like a switch: When SL2 is formed (~20% of the time), frameshifting occurs.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, our data indicate that the region corresponding to SL2 is conformationally flexible, adopting an SL2 stem with only a 20% probability. Consistent with our reported distribution of structural isoforms, Kelly et al use a reporter assay to suggest that the frequency of successful frameshifting in SARS-CoV-2 is about 20% (Kelly et al, 2020), indicating that the observed conformational variability of SL2 may be functional. Indeed, SL2 might function like a switch: When SL2 is formed (~20% of the time), frameshifting occurs.…”
Section: Discussionsupporting
confidence: 88%
“…The core of the SARS-CoV PRF, which shares an almost identical sequence with SARS-CoV-2, is predicted to form a three-stem pseudoknot comprised of SLI, SL2, and a pseudoknot helix, with an additional upstream attenuator stem that is poorly conserved in SARS-CoV-2 (Kelly et al, 2020). Our SHAPE reactivity and structure prediction are consistent with the existence of an attenuator stem, SL1, and the pseudoknot.…”
Section: Discussionsupporting
confidence: 77%
“…Our cryo-EM-guided data and modeling, along with recent results from several groups, suggest explanations for why FSE targeting efforts by us and others have so far yielded only modest inhibition of frameshifting and viral replication [4][5][6]34 . There is accumulating evidence that, in the full SARS-CoV-2 genome context, the FSE forms alternative structures involving genomic segments upstream of the element (Extended Data Fig.…”
Section: Discussionsupporting
confidence: 55%
“…Incomplete inactivation of coronavirus frameshifting and replication in these and prior studies motivated structural analysis to better understand the FSE. Despite prior expectations of structural heterogeneity and propensity for multimerization 4,45,52 , and despite having a size slightly under that of the previous smallest macromolecule imaged by cryo-EM ( We note two caveats regarding our cryo-EM analysis. First, the 6.9 Å resolution of the cryo-EM map is not sufficient to directly resolve base interactions, much less atom positions.…”
Section: Discussionmentioning
confidence: 82%
“…On the full-length gRNA itself, two partially overlapping open reading frames (ORF1a and ORF1b) are translated from the same start codon at the 5′ end, resulting in the polyproteins pp1a and pp1ab. Translation of the longer product pp1ab is made possible by a hairpin-type pseudoknot RNA s tructure known as the frameshifting element (FSE) which regulates a programmed -1 ribosomal frameshifting that overrides with about 50% efficiency the stop codon of ORF1a (Kelly et al, 2020;Namy et al, 2006) . Previous studies applied RNA structure probing techniques using s elective 2′-hydroxyl acylation analyzed by primer extension (SHAPE) and DMS, as well as nuclear magnetic resonance (NMR) to effectively identify conserved cis-acting RNA structures regulating the life cycle of coronaviruses.…”
Section: Introductionmentioning
confidence: 99%